Particle swarm optimization and Voronoi Diagram for wireless sensor networks coverage optimization - Ab Aziz, Nor Azlina; Mohemmed, Ammar W.; Sagar, B. S. Daya (IEEE Xplore, 2007)
The focus of this study is the sensor coverage problem. It is a crucial issue in Wireless Sensor Networks (WSN), where a high coverage rate will ensure a high quality of service of the WSN. This paper proposes a new algorithm to optimize sensor coverage using Particle Swarm Optimization (PSO). PSO is chosen to find the optimal position of the sensors that gives the best coverage and Voronoi diagram is used to evaluate the fitness of the solution.